Management of subtotal tracheal section with esophageal perforation: a catastrophic complication of tracheostomy - Caronia, Francesco Paolo; Fiorelli, Alfonso; Arrigo, Ettore; Santini, Mario; Castorina, Sergio (Journal of Thoracic Disease; Vol 8, No 5 (May 01, 2016): Journal of Thoracic Disease, 2016)
Herein, we reported a catastrophic condition as the almost complete rupture of trachea associated with esophageal lesion following an urgent surgical tracheostomy performed for unexpected difficult intubation. The extent of lesions required a surgical management. We decided against a resection and an end to end anastomosis but preferred to perform a direct suture of the lesion due to the presence of local and systemic infection. Then, the diagnosis of a tracheal fistula led us to perform a direct suture of the defect that was covered with muscle flaps. Actually the patient is alive without problems. Emergency situations as unexpected airway difficult intubation increase morbidity and mortality rate of tracheostomy also in expert hands. Sometimes these events are unpredictable. Mastery with a number of advanced airway technique should be sought when faced dealing with unexpected difficult intubations and written consent of such a concern should be given to the patient.